Development of Control and Monitoring System Arduino Uno based on AC Window: - - Erham, Eddy (ReTII, 2021)
Technological developments and concern for systems that are practical or energy efficient have encouraged researchers to make creative efforts and improvements to existing equipment and technology in various fields. This also includes in the AC field. In this research, the development of control and monitoring system for Window AC was carried out. For the design of the control system as the controller was used Arduino Uno. This Arduino was uploaded with the designed program. Meanwhile, the monitoring system was designed to use three ways, namely LCD, laptop and smartphone which were supported by Arduino, Labview and App Inventor software, respectively. The result is the control and monitoring system which is accurate and more attractive. The on-off control system applied to the window AC has a design error of 0.02 oC. And for AC that is in a high position, there is no need to go upstairs, because the setpoint and control differential can be adjusted via bluetooth